Toward an understanding of motivational influences on prospective memory using value-added intentions - Cook, Gabriel I.; Rummel, Jan; Dummel, Sebastian (Frontiers in Human Neuroscience, 2015)
This study examined value-added intentions by manipulating the cognitive frame associated with monetary contingencies for detecting prospective memory (PM) cues. We associated a loss-frame with a monetary punishment for failing to respond to cues and a gain-frame with a monetary reward for remembering to respond to cues and compared those frames to a no-frame control condition with no contingency linked to performance. Across two experiments, we find increased PM performance for participants in the loss-frame (Experiments 1 and 2) and in the gain-frame (Experiment 2) conditions relative to the no-frame condition. This value-related improvement in PM was not accompanied by a significant increase in cue monitoring as measured by intention-induced interference to an ongoing task and recognition memory for ongoing-task items. The few previous studies investigating motivational PM showed mixed results regarding whether PM improves due to incentives or not. Our results provide further evidence that, under some experimental conditions, PM improves with rewards and that the benefit generalizes to penalizing performance. The results have both practical implications and theoretical implications for motivation models of PM.